An architecture for a web service based product configuration information system - de Castro, Antonio Arrais (2010)
Competition in the today's global economy is intensifying the use of the new paradigm of mass customization. Such a paradigm is characterized by the need to deal with a very large variety of products determined by a substantial increase in customer specific product requirements. Implementing this paradigm requires agility and effectiveness in the customer-producer interaction and also in the order-production-delivery cycle. Web-based product configurators can provide an opportunity for improved interaction between producer and customer, and for a more formal, agile and effective process of both product and customer orders specification. In this paper, we propose architecture and describe the functionalities of a web based system for interactive product and customer order configuration. The proposed system can be also of value for supporting product data management and the production and delivery functions.